2021
DOI: 10.3390/cancers13153888
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia Mediates Paraspeckle Protein-1 Upregulation in Sleep Apnea

Abstract: As some evidence suggests that hypoxia might be an inducer of nuclear paraspeckle formation, we explore whether intermittent hypoxia (IH)-mediated paraspeckle protein-1 (PSPC1) overexpression might contribute to the activation of tumor growth factor (TGF)β-SMAD pathway in patients with obstructive sleep apnea (OSA). This activation would promote changes in intracellular signaling that would explain the increased cancer aggressiveness reported in these patients. Here, we show that patients with OSA exhibit elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
1
5
0
1
Order By: Relevance
“…Moreover, we found that IH could be underlying SMAD4 upregulation in OSA patients, since in vitro exposure to IH is capable of inducing SMAD4 upregulation in healthy monocytes, contributing to its release to the extracellular space in a HIF-1α dependent manner. These results are in line with previous studies reporting an upregulation of the TGF-β/Smad4 pathway upon IH conditions both in in vitro and animal models [23,35,56]. Taken together, this data suggests monocytes as the potential source of sSMAD4 in the plasma.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, we found that IH could be underlying SMAD4 upregulation in OSA patients, since in vitro exposure to IH is capable of inducing SMAD4 upregulation in healthy monocytes, contributing to its release to the extracellular space in a HIF-1α dependent manner. These results are in line with previous studies reporting an upregulation of the TGF-β/Smad4 pathway upon IH conditions both in in vitro and animal models [23,35,56]. Taken together, this data suggests monocytes as the potential source of sSMAD4 in the plasma.…”
Section: Discussionsupporting
confidence: 92%
“…In this context, a plethora of studies showed that TGFβ1/Smad signaling pathway played a central role in cardiovascular and cerebrovascular diseases, including atherosclerosis [16,17,[44][45][46][47]. Interestingly, it is reported that the TGF-β pathway is upregulated in OSA patients, and its activity is related to the hypoxemia severity [23,24,[48][49][50][51]. Although TGF-β has been classically defined as an anti-inflammatory cytokine, its role in inflammation has been recently reviewed [27,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now widely accepted that hypoxia enhances the malignant properties of tumors, and can strongly influence tumor growth, differentiation and migration [ 69 , 70 ]. Several studies have identified specific patterns of miRNA dysregulation in human cancers, including melanoma [ 61 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Así, se ha descrito que los pacientes apneicos jóvenes y no obesos experimentan una mayor activación de la cadena de señalización intracelular TGF-β-SMAD, que constituye una de las principales vías reguladoras de la progresión de células cancerígenas 13 . Este efecto parece deberse a la mayor inducción, mediada por la hipoxia intermitente, de la expresión de PSPC1 (paraspeckle component 1), un integrante de la cromatina del núcleo celular que regula la transición epitelio-mesénquima y la adquisición de características similares a las CSC (cancer stem cells), elementos clave para el desarrollo de metástasis 14 . Este fenómeno también resulta relevante en enfermos con un cáncer ya establecido.…”
Section: Patología Respiratoriaunclassified